2015
DOI: 10.1515/bpasts-2015-0090
|View full text |Cite
|
Sign up to set email alerts
|

Handling fuzzy systems’ accuracy-interpretability trade-off by means of multi-objective evolutionary optimization methods – selected problems

Abstract: Abstract. The paper addresses several open problems regarding the automatic design of fuzzy rule-based systems (FRBSs) from data using multi-objective evolutionary optimization algorithms (MOEOAs). In particular, we propose: a) new complexity-related interpretability measure, b) efficient strong-fuzzy-partition implementation for improving semantics-related interpretability, c) special-coding-free implementation of rule base and original genetic operators for its processing, and d) implementation of our ideas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Initial deployments of narrowband radio (NR) have been undertaken at the late 2019, with the focus on the use of the 3GPP version of . For mMTC, NR is accomplished by Narrow Band Internet of ings (NB-IoT) machine-type communications technologies in 3GPP that provide incomparable low-power broad-ranging performances that cover the wide spectrum of data rates and implementation scenarios [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Initial deployments of narrowband radio (NR) have been undertaken at the late 2019, with the focus on the use of the 3GPP version of . For mMTC, NR is accomplished by Narrow Band Internet of ings (NB-IoT) machine-type communications technologies in 3GPP that provide incomparable low-power broad-ranging performances that cover the wide spectrum of data rates and implementation scenarios [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of multi-objective optimization methods into the design process of the AC-DC converter allows to increase the system's efficiency, reliability and functionality, and can further help to maintain the desired level of cost of the system. This approach is currently developed in many research centers around the world and reported by many authors [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The research on the subject is being continued and will be integrated with a multi-objective optimization [17,18] process of the GC, where not only hardware, but also software assumptions have an impact on overall efficiency, reliability, and functionality of the GC. This paper is focused on GC operated as SAPF, and it is organized as follows: an introduction with problem description and basics knowledge about SAPF and its control requirements, a brief overview of literature regarding power quality, FL, the IoT and its multidisciplinary character, the main issues and the thesis of the paper, and the paper contest.…”
Section: Introductionmentioning
confidence: 99%